Impact of sedimentation on groundwater recharge at Sahalanowt Dam, Salalah, Oman. Technical note - Prathapar, Sanmugam A.; Bawain, A.A. (Informa UK Limited, 2014)
Recharge dams in Oman detain floods to recharge groundwater. The impact of sedimentation on recharge at Wadi Sahalanowt Recharge Dam, in Salalah, Oman, was evaluated using field data and numerical modelling. Analysis of the thickness of sediments after flood events shows that maximum depositions were at the same locations after each event, coinciding with the lowest positions in the wadi. Numerical modelling suggests that the current practice of periodic removal of sediments will restore the storage capacity of the reservoir, but that ploughing or raking of the underlying native sedimentary rocks could be required to significantly improve infiltration rates.